Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai - Nunik Kusumawati; Apid Hapid Maksum (Universitas Pakuan, 2026)
THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE This study aims to analyze the effect of work motivation and work discipline on employee performance at CV. Amanda Jaya. The study is motivated by the important role of human resources in supporting organizational success and the indication of declining employee performance influenced by low work motivation and work discipline. Work motivation serves as a driving force that encourages employees to perform their duties with enthusiasm and responsibility, while work discipline reflects employees’ compliance with organizational rules, regulations, and work standards. This research employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to all employees who served as research respondents. The research instruments were tested for validity and reliability to ensure the appropriateness of the measurement tools used. Furthermore, the data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that work motivation has a positive effect on employee performance. Employees with higher levels of motivation tend to demonstrate better performance in carrying out their duties and responsibilities. Work discipline also has a positive effect on employee performance and was found to be the more dominant factor in improving performance. In addition, work motivation and work discipline simultaneously contribute to enhancing employee performance. These findings suggest that employee performance can be improved through organizational efforts to strengthen employee motivation and consistently enforce work discipline. Therefore, management should pay greater attention to these aspects in order to enhance productivity and support the achievement of organizational goals effectively and efficiently.